EDUCATIONAL STRATEGIES FOR ENHANCING NURSE PRACTICES IN MANAGING SEVERE POSTPARTUM HEMORRHAGE: EVIDENCE FROM A PESHAWAR-BASED INTERVENTION STUDY (The Research of Medical Science Review, 2025)
Postpartum hemorrhage (PPH) is a leading cause of maternal mortality, especially in low-resource settings. The effective management of PPH is critical to reducing maternal deaths, and nurses play a key role in the timely identification and intervention of this condition. This study evaluates the impact of an educational intervention on nurses' knowledge and practice regarding uterine balloon tamponade (UBT), a second-line intervention for severe PPH, in tertiary care hospitals in Peshawar, Pakistan. Using a quasi-experimental pretest-posttest design, 54 nurses were selected for the intervention, which consisted of weekly training sessions over eight weeks. Data analysis revealed significant improvements in both knowledge and practical application of UBT. Pre-intervention, only 1.9% of nurses had excellent knowledge, which increased to 85.2% post-intervention. Practical application of UBT also improved, with 100.0% of procedures being successful post-intervention. Despite the positive outcomes, challenges such as resource limitations and lack of management protocols remain barriers to the widespread application of UBT. The study concludes that educational interventions can significantly enhance nurses' clinical competencies and contribute to better maternal healthcare outcomes, though structural improvements are needed to further optimize PPH management.